1998
DOI: 10.1017/s0025315400044830
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic Distribution of Sea Lice Larvae, Lepeophtheirus Salmonis, in Killary Harbour, West Coast of Ireland

Abstract: The distribution of Lepeophtheirus salmonis larvae in Killary Harbour was investigated by taking plankton tows from a number of stations on a regular basis during the spring/summer period in 1995 and 1996. Current patterns, ovigerous lice loads on the resident fish and water temperature and salinity were also recorded during the study. Larvae were only found consistently at a station close to a salmon farm at the mouth of the harbour. In the inner harbour, close to the mouths of two rivers, larvae were recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 20 publications
5
47
0
Order By: Relevance
“…If, as this study and others suggest (Costelloe et al 1996, 1998a,b, Penston et al 2004, the majority of the sea louse nauplii recovered near fish farms (e.g. Stn C) are derived directly from Lepeophtheirus salmonis on farmed salmon, then L. salmonis control measures applied at the farm, such as fallow periods and treatments, would be expected to affect larval densities, particularly nauplius densities.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…If, as this study and others suggest (Costelloe et al 1996, 1998a,b, Penston et al 2004, the majority of the sea louse nauplii recovered near fish farms (e.g. Stn C) are derived directly from Lepeophtheirus salmonis on farmed salmon, then L. salmonis control measures applied at the farm, such as fallow periods and treatments, would be expected to affect larval densities, particularly nauplius densities.…”
Section: Discussionmentioning
confidence: 58%
“…Costelloe et al (1996) postulated that larvae released from lice on farmed salmon would have little effect on louse infestations outside the immediate environs of the farm. However, despite the possibility that some L. salmonis copepodids recovered in Loch Shieldaig might have been transported there from elsewhere, the bulk of the louse larvae would be expected to have been generated locally, as the largest farm in the area is located in this loch, and it is unlikely that L. salmonis larvae from sources other than the gravid L. salmonis on farmed salmon at Farm 1 would improve the correlation between recovered larval densities, particularly nauplius densities, and counts of gravid L. salmonis at Farm 1.If, as this study and others suggest (Costelloe et al 1996, 1998a,b, Penston et al 2004, the majority of the sea louse nauplii recovered near fish farms (e.g. Stn C) are derived directly from Lepeophtheirus salmonis on farmed salmon, then L. salmonis control measures applied at the farm, such as fallow periods and treatments, would be expected to affect larval densities, particularly nauplius densities.…”
mentioning
confidence: 69%
“…The project coincided with a period of unusually high rainfall (approximately 2200 mm in 2011; SEPA Lingerton data), compared to an average of 1750 mm (Edwards & Sharples 1986); regional averages have remained fairly stable over the last 25 yr (Met Office data not shown). It is thought that adult sea lice can-not survive long periods in freshwater (McLean et al 1990), and previous studies have found lice to be absent from surface waters during periods of heavy rainfall (Costelloe et al 1998), leading to the idea that they might migrate vertically to avoid this influx of freshwater. Particle-tracking simulations were run using identical forcing, but with particles assumed to inhabit layers 2 (mean depth 4.98 m) and 3 (mean depth 8.3 m; mean depth in layer 1 is 1.66 m), to determine whether vertical migration of larvae influenced dispersal patterns.…”
Section: Scenariosmentioning
confidence: 99%
“…Lepeophtheirus salmonis copepodids are stenohaline, suggesting their activity and survival would be severely compromised in waters of reduced salinity (Pike & Wadsworth 2000). Sporadic abundance around river mouths was negatively correlated with rainfall, suggesting that a decrease in salinity through increased rainfall reduces copepodid abundance (Costello et al 1998b). Heuch (1995) reported that Lepeophtheirus salmonis copepodids maintained in a linear salinity gradient aggregated in salinities of 19 to 24 parts per thousand (ppt) during light conditions, and in salinities as low as 15 to 17.2 ppt in darkness, despite having the option of high saline conditions.…”
Section: Introductionmentioning
confidence: 99%